PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA DENGAN SELF-EFFICACY SEBAGAI VARIABEL INTERVENING (Studi Pada Mahasiswa Fakultas Ekonomi & Bisnis Universitas Mulawarman) - Alfaini, Fadhila; Sanjaya, Arwin (LPPM Universitas Multi Data Palembang, 2025)
This study aims to determine the effect of Entrepreneurship Education on Entrepreneurial Intentions with Self-Efficacy as a mediator. Data were analyzed by path analysis. The number of samples was 85 student respondents from the Faculty of Economics & Business, Mulawarman University class of 2018 who had taken entrepreneurship courses. This study found that entrepreneurship education has a significant effect on entrepreneurial intentions, entrepreneurship education has a significant effect on self-efficacy, self-efficacy has a significant effect on entrepreneurial intentions, entrepreneurship education has a significant effect on entrepreneurial intentions through self-efficacy.